Constructing a poor of attention deficit in preschool children based on the fifth Diagnostic and Statistical Manual (DSM-5) - Khalat Kherulah khthr; Waleed Khaled Abdulkareem (Zanco Journal of Humanity Sciences)
After the researchers sensed the existence of a problem of distraction in some children, they conducted a research under the title of building a measure to determine the distraction of attention in children of pre-school age and based on the fifth guide of Diagnostic and Statistical Manual of Mental Disorders (DSM_5), where they chose a random stratified sample consisting of 644 Of the mothers and 322 of the teachers of children of pre-school age. And in the absence of an appropriate scale based on international standards, such as the (DSM_5) scale, so the researchers, based on the criteria found in the aforementioned guide, they made a list of signs of distraction among children of pre-school age, where they reached the results that pre-school children can have distraction, and this is because of their intensive training in those subjects that It is necessary to take them into account. And since the gender component is one of the important factors for the incidence of distraction, so the incidence of males is more than that of females.